2017
DOI: 10.1016/j.aca.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Off-line mixed-mode liquid chromatography coupled with reversed phase high performance liquid chromatography-high resolution mass spectrometry to improve coverage in lipidomics analysis

Abstract: The confident identification and in-depth profiling of molecular lipid species remain to be a challenge in lipidomics analysis. In this work, an off-line two-dimensional mixed-mode and reversed-phase liquid chromatography (RPLC) method combined with high-field quadrupole orbitrap mass spectrometer (Q Exactive HF) was developed to profile lipids from complex biological samples. In the first dimension, 22 different lipid classes were separated on a monolithic silica column with elution order from neutral to pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…It has been reported by Wang et al [28] that 372 lipids in plasma were identified by a stop-flow two-dimensional LC-MS method within 130 min, while the number of lipids identified was 284 using 1 D RPLC analysis. Narváez-Rivas et al [44] identified about 800 lipid species in rat plasma and rat liver by an offline two-dimensional mix-mode LC-RPLC-MS/ MS method about 7 h, and approximate 400 lipids by RPLC-MS method within 31 min [17]. However, in this study, there were over 1000 lipid species annotated using the HILIC×RPLC compared with RPLC-MS of about 400 annotated lipids.…”
Section: Number Of Annotated Lipid Speciesmentioning
confidence: 52%
“…It has been reported by Wang et al [28] that 372 lipids in plasma were identified by a stop-flow two-dimensional LC-MS method within 130 min, while the number of lipids identified was 284 using 1 D RPLC analysis. Narváez-Rivas et al [44] identified about 800 lipid species in rat plasma and rat liver by an offline two-dimensional mix-mode LC-RPLC-MS/ MS method about 7 h, and approximate 400 lipids by RPLC-MS method within 31 min [17]. However, in this study, there were over 1000 lipid species annotated using the HILIC×RPLC compared with RPLC-MS of about 400 annotated lipids.…”
Section: Number Of Annotated Lipid Speciesmentioning
confidence: 52%
“…Despite the proposed shorthand notation, there has been a mix of annotation styles present in literature. For example, of the lipidomics research articles published in 2017 determined on Science Direct (accessed 02/09/2017), 3 articles [29,32,33] incorrectly used “/”, 3 articles [3436] used “-”, and1article [37] used “_” between fatty acyl constituents, when positional isomers were not identified. One potential source of confusion in annotating lipids is that current lipid identification software, for example LipidSearch, MS-DIAL [38], LipidBlast [39], and Greazy [40] all employ “/”when fatty acyl positions are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Most lipid mediator-related studies employ C18-based columns to perform the separation; however, C30 column also showed great potential in separation of lipid molecular species [32,33] and could be used as an alternative for analyzing oxylipins. We compared the chromatographic performances of core-shell C30 and HSS T3 C18 column.…”
Section: Resultsmentioning
confidence: 99%